Financial, economic and social systems: French Regulation School, Social Structures of Accumulation and Post-Keynesian approaches compared - Eckhard Hein; Nina Dodig; Natalia Budyldina (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
This paper surveys some of the important literatures on financial, economic and social systems with an eye towards explaining the tendencies towards 'financialisation'. We focus on important strands of this literature: the French Regulation School, the US-based Social Structures of Accumulation approach, the contributions by several Post-Keynesian authors, with a focus on the long-run views contained in Hyman Minsky's work, in particular. In our comparative assessment of these approaches, we adopt the following four steps procedure: First, we sketch the basic structure of the approaches in order to single out how each of them views the interaction between social institutions and the economy and the related dynamics regarding the development of the institutional structure and the associated stages or regimes of economic development. Second, we describe how these approaches view the structural breaks or the regime shifts in the long-run development of modern capitalism, which has triggered or at least has contributed to the emergence of a type of capitalism dominated by finance (financialisation). Third, we outline how these different approaches view the main characteristics and features of financialisation. Fourth, we deal with the respective views on the consequences of financialisation for long-run economic and social development including the crisis of this stage of development.
Keywords: E02; E11; E12; G01; P10; P16; P51; 330; French Regulation School; Social Structures of Accumulation; Post-Keynesian approach; Minsky; financialisation; stages of capitalist development; finance-led growth regime; global neoliberal SSA; finance-dominated capitalism; money manager capitalism; financial; economic and social systems